2005
DOI: 10.1063/1.1884194
|View full text |Cite
|
Sign up to set email alerts
|

Fast microtomography using high energy synchrotron radiation

Abstract: At the High Energy Beamline ID15A at the European Synchrotron Radiation Facility we have developed a fast three-dimensional x-ray microtomography system, which acquires a complete dataset in typically less than 10s. This unprecedented speed is achieved by combining a high efficiency phosphor screen, a reflecting microscope objective and a fast charge coupled device detector with the very intense high-energy white beam radiation provided by a wiggler source. The achieved spatial resolution is 2μm. The available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
126
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 16 publications
0
126
1
Order By: Relevance
“…Absorption micro-tomography was performed using a high intensity filtered white x-ray beam. The tomography set-up is described in detail in [4].…”
Section: Combined Synchrotron Tomography and Powder Diffraction Durinmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption micro-tomography was performed using a high intensity filtered white x-ray beam. The tomography set-up is described in detail in [4].…”
Section: Combined Synchrotron Tomography and Powder Diffraction Durinmentioning
confidence: 99%
“…Modern synchrotron sources can provide brilliant, high energy x-ray beams, which permit the fast acquisition of tomograms of millimetre thick highly absorbing metallic samples. Due to the short acquisition time of less than a minute per tomogram, tomography experiments during in-situ HTs have recently become possible at the ID15A beamline at the European Synchrotron Radiation Facility (ESRF) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Around the year 2005 (Lambert et al, 2007) the scan time for a single tomographic volume was of the order of 10 min at a spatial resolution of 5-10 mm. Already then, it was, however, demonstrated that it was possible to acquire a tomogram in less than a minute (Di Michiel et al, 2005;Lambert et al, 2010), and today 20 tomographic scans may be acquired within 1 second (Mokso et al, 2013;dos Santos Rolo et al, 2014;Maire et al, 2016). With such an acquisition speed, a new set of challenges arose.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-fast radiography has been demonstrated at various beamlines [1,2,3,4] and a number of exciting applications has been successfully addressed [5]. Nevertheless the extreme demand on the mechanics, synchronisation and the detector prevents a straight-forward transition from 2D towards 3D ultra-fast imaging.…”
Section: Introductionmentioning
confidence: 99%